HUBUNGAN PENGETAHUAN DAN SIKAP KELUARGA DENGAN PENCEGAHAN DEMAM BERDARAH DENGUE (DBD) DI KELURAHAN MOGOLAING (JURNAL KEPERAWATAN, 2014)
Abstract: Dengue fever is a public health problem in Indonesia and still being up to date problem. Based on a survey of PHC Gogagoman health center that Mogolaing villages are with Dengue Fever cases with the highest number of 24 cases. Perpose: This study aims to determine the relation of knowledge and family attitude with the Prevention of Dengue hemorrhagic fever (DHF) in the Mogolaing district. Research Methods: This study was conducted with a cross-sectional method, the selection of samples with purposive sampling with a sample of 100 families. Research Outcome: Analysis of the data using statistical test Chi Square with a limit of significance Î± = 0.05. Based on test results obtained probability value for the relation with family knowledge with dengue fever prevention of 0.000 (p> 0.05), while for the relation of family attitude with dengue prevention is 0.002 (P 0,05), sedangkan untuk hubungan sikap keluarga dengan pencegahan demam berdarah dengue sebesar 0,002 (p